Ecthyma gangrenosum in a neonate - K., Vindhiya; C., Lakshmi Charan; D., Aishwarya; M., Sindhu (International Journal of Contemporary Pediatrics, 2017)
Ecthyma gangrenosum (EG) is a rare skin infection caused by pseudomonas aeruginosa. It typically occurs in immunocompromised and critically ill patients but can occur rarely in healthy children. 28 days old neonate presented with widespread vesiculobullous lesions which ruptured to form punched out gangrenous ulcers with black eschar. Blood and pus culture grew Pseudomonas aeruginosa and diagnosis of EG due to pseudomonas was made. Despite appropriate measures, baby succumbed to the illness. Rapid progression of the lesions and high mortality rate emphasize the importance of early suspicion and proper treatment.